Functions of repetition in two western languages: English and Spanish - Quesada Pacheco, Jorge Arturo (Universidad de Costa Rica, 2015)
El propósito de este estudio fue examinar las funciones de repetición en dos idiomas occidentales: Inglés y Español. Se argumenta que el uso de Johnstone de un solo idioma para establecer un contraste entre el árabe y lenguas occidentales, Inglés, plantea dos cuestiones importantes. 1) ¿Son todas las lenguas occidentales por igual? 2) ¿Cuáles son las funciones de repetición en Inglés y cómo se comparan con o contraste con los tipos y funciones de repetición en español? Estas cuestiones se abordan en este estudio.The purpose of this study was to examine the functions of repetition in two Western languages: English and Spanish. We argue that Johnstone's use of only one language to establish a contrast between Arabic and Western languages, English, raises two important questions. 1) Are all Western languages alike? 2) What are the functions of repetition in English and how do they compare to, or contrast with types and functions of repetition in spanish? These questions are addressed by this study.